2009
DOI: 10.1167/iovs.08-2455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the X-Linked High-Grade Myopia Locus (MYP1) with Cone Dysfunction and Color Vision Deficiencies

Abstract: Purpose X-linked high myopia with mild cone dysfunction and color vision defects has been mapped to chromosome Xq28 (MYP1 locus). CXorf2/TEX28 is a nested, intercalated gene within the red-green opsin cone pigment gene tandem array on Xq28. The authors investigated whether TEX28 gene alterations were associated with the Xq28-linked myopia phenotype. Genomic DNA from five pedigrees (with high myopia and either protanopia or deuteranopia) that mapped to Xq28 were screened for TEX28 copy number variations (CNVs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Connexin36 is essential in the transmission of rod-mediated visual signals in the mammalian retina (167,168). Evidence of photoreceptor-mediated susceptibility to myopia has previously been noted in rare X-linked disorders in which cone and/or rod function is disrupted (169)(170)(171)(172)(173)(174). To our knowledge, however, the association of a variant near GJD2 is the first evidence of a possible role for modulators of retinal visual signals in susceptibility to common refractive errors.…”
Section: Candidate Region and Genome-wide Association Studiesmentioning
confidence: 99%
“…Connexin36 is essential in the transmission of rod-mediated visual signals in the mammalian retina (167,168). Evidence of photoreceptor-mediated susceptibility to myopia has previously been noted in rare X-linked disorders in which cone and/or rod function is disrupted (169)(170)(171)(172)(173)(174). To our knowledge, however, the association of a variant near GJD2 is the first evidence of a possible role for modulators of retinal visual signals in susceptibility to common refractive errors.…”
Section: Candidate Region and Genome-wide Association Studiesmentioning
confidence: 99%
“…Moreover, copy number variations of SLITRK2 have been associated with X-linked high myopia (near/shortsightedness) (Metlapally et al 2009 ), and SLITRK2 is also a potential candidate gene for development of dyslexia (Huc-Chabrolle et al 2013 ). However, all these potential relationships need to be confi rmed or deconfi rmed with further investigations.…”
Section: Diseasesmentioning
confidence: 99%
“…Until recently, it remained unclear which gene was responsible for these defects, but work conducted by Metlapally et al has suggested one gene candidate: TEX28 (35). To better understand the role of the proposed gene, one has to first appreciate that the visual cone pigment (opsin) genes comprise a contiguous array in which a red (L) gene is followed by one or more copies of the green (M) gene.…”
Section: X-linked Locimentioning
confidence: 99%
“…Normally, there are 3 repetitive copies of TEX28 that are intercalated within and translated in the opposite sense to the opsin gene array (37). What Metlapally et al demonstrated is that in 5 high myopic pedigrees there were one fewer, or 4 or 5 copies of TEX28 (35). The phenomenon of copy number variants (CNV) has been proposed as a factor in disease inheritance and susceptibility as it affects "gene dosage," and thus could be the cause of high myopia in this X-linked locus.…”
Section: X-linked Locimentioning
confidence: 99%